Gestational trophoblastic neoplasia following molar ectopic pregnancy: A case report - Soares, Patrícia Daniela Paranhos B.; Costa, Olívia Lúcia Nunes; Costa, Ludmila Andrade; Maestá, Izildinha [UNESP] (My University, 2008)
BACKGROUND: Ectopic molar pregnancy is a gestational trophoblastic disease (GTD) of rare occurrence and therefore not always remembered as a diagnostic possibility. CASE: We describe a case of molar ectopic pregnancy in a primiparous woman who developed gestational trophoblastic neoplasia and required chemotherapy to achieve remission. CONCLUSION: This case stresses the important role of histopathologic examination in establishing a diagnosis of ectopic molar pregnancy. Moreover, close follow-up of human chorionic gonadotropin levels is required when a GTD is suspected. © Journal of Reproductive Medicine®, Inc.
Keywords: Chemotherapy; Gestational trophoblastic disease; Molar ectopic pregnancy